Pengaruh Penambahan Serbuk Kulit Pisang Pada Semen Portland Dalam Berbagai Persentase Terhadap Kuat Tekan Beton - Ilham Setiawan; Yudi Setio Prabowo (Jurnal Konstruksi, 2026)
Concrete is a commonly used construction material due to its high strength and durability. However, the use of cement as the primary component of concrete results in significant carbon emissions. This study aims to examine the effect of adding banana peel powder as an additive and partial cement substitute on the compressive strength of concrete. The method used was an experiment with variations in banana peel powder content of 0%, 1%, and 5%. Cube-shaped test specimens measuring 15 cm × 15 cm × 15 cm were tested for compressive strength at 7 and 14 days of age. The results showed that adding 1% banana peel powder significantly increased the compressive strength of the concrete compared to normal concrete, reaching 15.7 MPa at 7 days and 18.85 MPa at 14 days. However, the addition of 5% actually reduced the compressive strength. Meanwhile, partially replacing cement with banana peel powder tended to reduce concrete strength in all variations. In conclusion, the use of 1% banana peel powder as an additive is the most optimal variation for increasing concrete compressive strength, whereas its use as a cement substitute is not recommended